2020
DOI: 10.1097/md.0000000000023330
|View full text |Cite
|
Sign up to set email alerts
|

Bringing prevost's sign into the third dimension: Artificial intelligence estimation of conjugate gaze adjusted length (CGAL) and correlation with acute ischemic stroke

Abstract: Conjugate gaze deviation is associated with acute ischemic stroke (AIS), although previously only measured on a 2D plane. The current study evaluates 3D imaging efficacy to assess conjugate gaze deviation and correlate direction and strength of deviation to neuro-clinical findings. A retrospective analysis of 519 patients who had CT scans for suspected AIS at our institution. Direction and angle of eye deviation were calculated based on 2D axial images. Volumetric reconstruction of CT scans allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Selective laser melting (SLM), one of the AM technologies, enables the fabrication of space-filling lattice structures with exceptional load-carrying capacity, customizable stiffness, controlled cell topology, cell size, and porosity. In work [14], the Schoen Gyroid (SG) unit cell, a periodic surface structure, was used to design the cell structures. The authors showed that the mechanical responses of cellular structures could be accurately described with FEM.…”
Section: Introductionmentioning
confidence: 99%
“…Selective laser melting (SLM), one of the AM technologies, enables the fabrication of space-filling lattice structures with exceptional load-carrying capacity, customizable stiffness, controlled cell topology, cell size, and porosity. In work [14], the Schoen Gyroid (SG) unit cell, a periodic surface structure, was used to design the cell structures. The authors showed that the mechanical responses of cellular structures could be accurately described with FEM.…”
Section: Introductionmentioning
confidence: 99%